PENGEMBANGAN FLASHCARD INTERAKTIF BERBASIS KUIS SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP - Fatimah Az Zahrah (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This research aims to develop interactive learning media in the form of quiz-based flashcards designed to increase student motivation, engagement, and understanding of Islamic Religious Education (PAI) material at the Junior High School (SMP) level. The flashcards are available in both digital and printed formats and feature interactive quizzes that allow students to review the material independently and enjoyably. The research method used a Research and Development (R&D) approach with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. Results from expert validation and limited trials indicate that the developed media is highly feasible for use. This media has also been shown to improve student understanding based on pretest and posttest results. This research makes a significant contribution to the development of innovative and contextual PAI learning media.